From empire to republic - Bahar, Hacer. (Berlin)
85 sayfa
Keywords: “This book focuses on American missionary activities in the Ottoman Empire. After the construction of the American Board of Commissioners for Foreign Mission in 1810, American missionaries started to spread the Gospel around the world. The Ottoman Empire was perceived as a strategic place since it occupied Jerusalem. By the time they arrived, American missionaries found a weak central authority. Some of the Ottoman officials considered that Westernization of the public institutions in the Empire could strengthen central authority. In order to protect its integrity, the Ottoman Empire started to grant freedoms to the minorities. After gaining liberties, American Missionaries further strengthened their position in the Empire. This book analyzes the strong image of American missionary schools through Robert College which was established in 1863. Robert College which reflects American ideals, preserves its distinguished place to this day.” --